Hormone-dependent control of developmental timing through regulation of chromatin accessibility - Uyehara, Christopher M. (Genes Dev, 2017)
Specification of tissue identity during development requires precise coordination of gene expression in both space and time. Spatially, master regulatory transcription factors are required to control tissue-specific gene expression programs. However, the mechanisms controlling how tissue-specific gene expression changes over time are less well understood. Here, we show that hormone-induced transcription factors control temporal gene expression by regulating the accessibility of DNA regulatory elements. Using the Drosophila wing, we demonstrate that temporal changes in gene expression are accompanied by genome-wide changes in chromatin accessibility at temporal-specific enhancers. We also uncover a temporal cascade of transcription factors following a pulse of the steroid hormone ecdysone such that different times in wing development can be defined by distinct combinations of hormone-induced transcription factors. Finally, we show that the ecdysone-induced transcription factor E93 controls temporal identity by directly regulating chromatin accessibility across the genome. Notably, we found that E93 controls enhancer activity through three different modalities, including promoting accessibility of late-acting enhancers and decreasing accessibility of early-acting enhancers. Together, this work supports a model in which an extrinsic signal triggers an intrinsic transcription factor cascade that drives development forward in time through regulation of chromatin accessibility.